Bioactivity-Guided Fractionation of the Traditional Chinese Medicine Resina Draconis Reveals Loureirin B as a PAI-1 Inhibitor. (18th September 2017) - Jiang, Yu; Zhang, Guangping; Yan, Dong; Yang, Hong; Ye, Zuguang; Ma, Tonghui
Abstract : Thrombotic diseases have become a global burden due to morbidity, mortality, and disability. Traditional Chinese medicine has been proven effective in removing blood stasis and promoting blood circulation, but the exact mechanisms remain unclear. Plasminogen activator inhibitor-1 (PAI-1) is a natural inhibitor of tissue-type and urokinase-type plasminogen activators. In this study, we screened four fractions of Resina Draconis (a traditional Chinese medicine) extract for PAI-1 inhibitory activity. Bioactivity-guided purification and chromogenic substrate-based assay led to the identification of loureirin B as the major PAI-1 inhibitor, with an IC50 value of 26.10  μ M. SDS-PAGE analysis showed that formation of the PAI-1/uPA complex was inhibited by loureirin B, and the inhibitory effect of loureirin B on PAI-1 was also confirmed by clot lysis assay. In vivo studies showed that loureirin B significantly prolonged the tail bleeding time and reduced the weight and size of arterial thrombus, reduced hydroxyproline level, and partly cured liver fibrosis in mice. Taken together, the results revealed loureirin B as a PAI-1 inhibitor, adding a new pharmacological target for loureirin B and uncovering a novel mechanism underlying the antithrombotic property of Resina Draconis, which might be useful in the treatment of cardiovascular diseases such as thrombosis and fibrosis.